Pengaruh Pengelolaan Kearsipan Terhadap Efisiensi Kerja Pegawai Negeri Sipil Di Kantor Perwakilan Badan Pengawasan Keuangan Dan Pembangunan Propinsi Sulawesi Utara - Maengkom, Valine Mei; Mandey, Jantje; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : This study was motivated by the problems found in the office of Representatives Financialand Development Supervisory Agency Sulawesi province, namely in archival management activities notwell ordered. The constraints faced is the maintenance of records that there are still records that arestacked in nature resulting in the archive warehouse perishables and also difficult to be rediscovered whenneeded any time. This of course can hinder the work of the office. It is therefore necessary to have a goodarchival management and organized so as to make it easier for employees to find back the archive in a fasttime. Structuring the archive is one aspect that should be applied in the office to support the achievementof the objectives of productivity improvement and efficiency of office work. Thus communications officerjob will run more smoothly, so that the coordination and supervision easier. The purpose of this study wasto determine the archival management know is there any influence on the efficiency of employees workingin the Office of Finance and Development Supervisory Board of North Sulawesi Province. In this study,the method used is quantitative analysis method. While data analysis technique used is the technique ofcorrelation between variables to prove the influence of archival management towards employee workefficiency. Based on the results of research conducted and followed by analyzing the data obtained, thenthe result is that there is a very strong relationship between the management of archival against theworking efficiency of employees amounted to 0.943 and this means working hypothesis or alternativehypothesis is accepted, this means there are positive influence between management archival against theworking efficiency of employees with the level of influence of 88.90%. So the hypothesis that there is aninfluence on the efficiency of the management of archivesKeywords : Work Efficiency